2017
DOI: 10.7324/japs.2017.71102
|View full text |Cite
|
Sign up to set email alerts
|

Hesperidin protects against diethylnitrosamine/carbon tetrachloride-induced renal repercussions via up-regulation of Nrf2/HO-1 signaling and attenuation of oxidative stress

Abstract: The kidney plays a central role in detoxification and excretion of toxic metabolites, and therefore is susceptible to toxicity by xenobiotics. Hesperidin is a citrus flavonoid with multiple beneficial therapeutic effects. Here, we investigated the possible modulatory effect of hesperidin on diethylnitrosamine (DEN)/carbon tetrachloride (CCl4)-induced nephrotoxicity in rats, pointing to the role of Nrf2/HO-1 signaling. Male Wistar rats received a single intraperitoneal injection of DEN. Two-weeks later, the DEN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) levels which agree with Bojan et al, 10 Silke 54 and Nishiumi et al 55 oxidative stress by stimulating the antioxidant defenses. [56][57][58][59] In this study, D-GalN induced rats exhibited declined Nrf2 gene expression. This decline is in agreement with previous studies 58,60,61 who reported that excessive free radicals production caused a decrease in Nrf-2 expression.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) levels which agree with Bojan et al, 10 Silke 54 and Nishiumi et al 55 oxidative stress by stimulating the antioxidant defenses. [56][57][58][59] In this study, D-GalN induced rats exhibited declined Nrf2 gene expression. This decline is in agreement with previous studies 58,60,61 who reported that excessive free radicals production caused a decrease in Nrf-2 expression.…”
Section: Discussionmentioning
confidence: 49%
“…[56][57][58][59] In this study, D-GalN induced rats exhibited declined Nrf2 gene expression. This decline is in agreement with previous studies 58,60,61 who reported that excessive free radicals production caused a decrease in Nrf-2 expression. This effect that was significantly reversed in algal extract or/and IR treated groups which may be attributed to free radicals scavenging, inflammation suppression and restoring oxidative balance.…”
Section: Discussionmentioning
confidence: 49%